The Perceived Impact of the LGU-Funded Extension Programs in Ilocos Sur Polytechnic State College – Santiago Campus - Dela Cruz, Jonathan L.; Estrañero, Adela G.; Rante, Jona A. (Future Science / FSH-PH Publications, 2023)
Empowering people through the implementation of sustainable community development programs is one of the prime concerns of Higher Education Institutions (HEI). Through responsive extension programs and services of HEIs and strong partnerships with LGUs, the people are empowered, socioeconomic status is uplifted and the cultural heritage is conserved. This study aimed to assess the impact of the LGU-Funded extension programs of a State Higher Institution in the Philippines. This descriptive research study used a questionnaire and interview with 180 beneficiaries and utilized mean and rank. The results revealed that extension program implementers are highly capable in terms of leadership, personnel, and financial capability. The participation of LGUs and community people is high. In addition, the level of program outputs of the extension services is satisfactory and the impact of the extension programs is rated satisfactory. Hence, the partnership between the LGU and the academe and funding of the extension programs and activities by LGUs shall be sustained. The adoption and implementation of the extension improvement plan is proposed.